PENGARUH WAKTU TUNGGU DI LOKET PENDAFTARAN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI PUSKESMAS AIKMEL TAHUN 2022 - Julianto, Julianto; Syatriawan Perdana Putra2 (Nusadaya Journal of Multidiciplinary Studies, 2022)
This study aims to determine the effect of patient waiting time at the registration counter on the level of patient satisfaction at the Aikmel Health Center in 2022. The method in this study used in the form of observation and questionnaires with the object of research being outpatients at Aikmel Public Health Center, totaling 97 respondents. The researcher gave questionnaires to the respondents as a data collection tool to determine the effect of patient waiting time at the registration counter on the level of patient satisfaction at the Aikmel Health Center in 2022. The data used in this study were primary data and secondary data. The analytical test used is the chi square test to determine the correlation or relationship between two variables. Testing is done by using SPSS 16 software for windows. The results showed that most of the outpatients stated that the waiting time at the Aikmel Health Center had met the standard and for outpatient satisfaction, most of the patients were satisfied. The results of the chi square test show that p value = 0.000 <0.05, which means that there is an influence between waiting time on outpatient satisfaction at Aikmel Health Center. It can be concluded that there is an effect of waiting time at the registration counter on outpatient satisfaction at the Aikmel Health Center in 2022.